ENERGY TRANSITION IN SOUTH SUMATRA: NON-EXTRACTIVE SECTORS AND GREEN ECONOMY POLICY STRATEGIES - Fadhlia, Maudy Noor; Setiawan, Roy; Supli, Nur Aslamiah; Nuaba, I Kadek Andre (Sosiohumaniora, 2026)
South Sumatra faces a structural challenge in reducing its dependence on coal, oil and gas while maintaining regional growth and employment. This study examines which non-extractive sectors can support a locally grounded energy transition and what policy strategies the provincial government can implement under fiscal and institutional constraints. The study uses a convergent parallel mixed methods design. Quantitative data were drawn from Statistics Indonesia, Bank Indonesia, regional planning documents, renewable energy capacity data, and the SDG Index and Dashboard. Qualitative data were obtained from semi-structured interviews with Bappeda South Sumatra, IESR, and WRI Indonesia, supported by policy document analysis. The analysis applies the multi-level perspective, political economy of energy transition, and energy justice to connect landscape pressure, fossil-based regional regimes, niche innovations, and distributional risks. The findings show three core results. First, coffee, rubber, palm oil-based bioenergy, fisheries, and nature-based tourism are the most feasible non-extractive sectors because they combine local resource endowment, employment potential, value-added opportunities, and policy support. Second, renewable energy development remains at an early stage, with Rp1.2 trillion in accumulated investment from 2020 to 2024, 3.8 MW rooftop solar PV capacity, 12.5 MW biomass and biogas capacity, and 85 MW untapped micro-hydro potential. Third, the main transition barrier is not only technical capacity, but also fragmented coordination, limited fiscal incentives, weak green investment instruments, and social dependence on coal-related micro-businesses in mining regions. The study recommends a dedicated regional energy transition unit, an integrated action roadmap linked to RPJMD and RUED, green financing instruments, post-mining land repurposing, and community-based energy literacy. These findings strengthen the scientific understanding of subnational energy transition in resource-dependent provinces and provide practical policy guidance for SDG 7, SDG 8, SDG 9, and SDG 13.